The Role of For-Profit Hospitals in Medical Expenditures : Evidence from Aggregate Data in China - Liu, G.G. (2012)
The health care delivery system in China, which is dominated by state hospitals, is being increasingly challenged by public concerns: it is too expensive and too inaccessible, a complaint commonly phrased as "kai bin nan, kan bin gui" in Chinese. As the penetration of for-profit hospitals has gradually increased, there is a growing need for policy research to assess their impact oil medical spending from the patient perspective. Using panel data at the provincial level in China, this paper examines the impact of the penetration of for-profit hospitals on average medical expenditures for both outpatient and inpatient services in public general hospitals. Based on fixed-effect model estimates, the study shows that the penetration of for-profit hospitals has lowered the average medical expenditures for both inpatient and Outpatient services across regions, especially for pharmaceuticals. Together with other results, this study finds no evidence that private for-profit hospitals drive up average medical expenditures while serving their profit-maximization objectives. Rather, they help increase the market supply of health care, which in turn better serves the increasing demand. (C) 2009 Elsevier Inc. All rights reserved.